SEMIOTICS ANALYSIS STREET PHOTOGRAPHY ON THE BOOK “STREET PHOTOGRAPHY DENGAN PONSEL” BY PAUL ZACHARIA - Hanna Luthfiani; Renny Triwardani; Siti Fatonah (The Indonesian Journal of Communication Studies, 2017)
Street Photography is one of the most popular photography genres in today’s society. The camera on smarthphone became one of the alternative photographer in producing street photography works. The book became the media used to present the work of street photography by Paul Imam Zacharia. Street photography in this study focuses on public space. Semiotics analysis is used to read the meanings or signs present in this study by combining Charles Pierce’s semiotic theory and public space theory Jurgen Habermas. Semiotics theory shows the existence of three signs namely icons, indexes, and symbols that will be understood in the public space. Data collection techniques using documentation, literature study, and interviews. The data validity uses three of nine formulas: communicator, physical and social context, and common sence. The results show that Paul Imam Zacharia’s street photography works have meaning in depiction of activities in public space such as functional utilization of public space. In addition there are icons, indexes, and symbols that become a hint that the object taken by Paul Imam Zacharia is a public space. Signs and meanings formed in the work depict non-verbal communication that is visualized and will be represented by every individual who sees the work.